Linking leaders’ toxic leadership behaviors to employee attitudes and behaviors - Büyükyılmaz, Ozan; Kara, Cihan (Serbian Journal of Management, 2024)
The aim of this research is to examine the detrimental impacts of toxic leadership behaviors displayed by managers on their subordinates. Specifically, the study investigates the effects of toxic leadership behaviors such as lack of appreciation, self-interest, selfishness, and negative spiritual state, as perceived by employees, on various organizational outcomes including affective commitment, job satisfaction, organizational identification, perceived job performance, and turnover intention. A total of 419 employees working in public or private institutions completed a questionnaire to collect the data. The study first assessed the reliability and validity of the measurement scales and then tested the proposed hypotheses utilizing path analysis within the framework of structural equation modeling. The results of the study indicate that lack of appreciation, self-interest, and selfishness have significant predictive effects on different employee attitudes and behaviors, whereas negative spiritual state does not significantly affect employee attitudes and behaviors. Consequently, the study demonstrates that toxic leadership negatively affects affective commitment, job satisfaction, organizational identification, perceived job performance, and increases the intention to leave. The findings provide important insights for scholars and practitioners alike, and can be used to develop strategies to mitigate the negative effects of toxic leadership on employees and organizations.